Examining internet banking acceptance: a comparison of alternative technology adoption models. (4th January 2010) - Lai, Vincent S.; Chau, Patrick Y.K.; Cui, Xiling
Technology acceptance has been widely researched in the past two decades, resulting in the development of a cumulative tradition in the Information Systems (ISs) discipline. Two theories commonly applied to investigate technology acceptance are the Diffusion of Innovation (DOI) theory and the Technology Acceptance Model (TAM). These two models/theories may complement and supplement each other in their theoretical capacity and capability. This paper integrates DOI with TAM and evaluates their capacity in the context of internet banking acceptance. Our findings suggest that the proposed integrated model is significantly better in explaining the variance in internet banking acceptance than either the DOI or the TAM alone.